Application of communicative approach techniques to develop speaking skills in students of high school during the school year 2018-2019 - Chuya Chuya, Wilmer Adolfo (2019)
In these last decades, it has emerged in the educational environment school the figure of the teacher tutor, an educator who stays close to the students in their daily teaching-learning processes, intervening also in other areas that are not indifferent in the life of the person, such as affective containment in certain cases, the detection of problems in the relational dimension of the members of the group, pointing out possible directions in a process of vocational guidance, without neglecting the indispensable testimony in order to form values. This educational project has the title “application of communicative approach techniques to develop speaking skills in students of high school during the school year 2018-2019”…..